2004
DOI: 10.1017/s0265021504009123
|View full text |Cite
|
Sign up to set email alerts
|

Pain control with low-dose alfentanil in children undergoing minor abdominal and genito-urinary surgery

Abstract: It was concluded that a low-dose, intravenous bolus of alfentanil may be an efficient alternative to peripheral nerve blockade in controlling pain during and after minor abdominal and genito-urinary surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 19 publications
0
4
0
Order By: Relevance
“…Below are some suggestions regarding dosing of some of the drugs that may be applicable to the different pain management ladder levels based on the available literature . Table shows dosage suggestions for systemic analgesia, special care must be taken when prescribing opiods in patients with obstructive sleep apnea.…”
Section: Recommendationsmentioning
confidence: 99%
“…Below are some suggestions regarding dosing of some of the drugs that may be applicable to the different pain management ladder levels based on the available literature . Table shows dosage suggestions for systemic analgesia, special care must be taken when prescribing opiods in patients with obstructive sleep apnea.…”
Section: Recommendationsmentioning
confidence: 99%
“…41 Pain in connection with genito-urinary infections is quite often described. 42 Catheter-associated urinary tract infection is the most common nosocomial infection, accounting for more than one million cases every year in American hospitals and NHs. 43 A large-scale epidemiological study in The Netherlands has shown that orofacial pain has an increasing incidence rate with age for most of the pain diagnoses in the general population, with rates as high as 30.6 for trigeminal neuralgia and 44.2 for post-herpetic neuralgia.…”
Section: Pain Prevalence In Nursing Home Patientsmentioning
confidence: 99%
“…Living in a NH, 53% of patients are at risk of developing a pressure ulcer (Horn et al, 2002), and skin diseases found in 95% of the patients were described as one of the most prevalent health problems (Black et al, 2006). Pain in connection with genito-urinary infections is quite often described (Leoni et al, 2004). Catheter-associated urinary tract infection is the most common nosocomial infection, accounting for more than one million cases every year in American hospitals and…”
Section: Pain In Internal Organs the Head And Skinmentioning
confidence: 99%